Possibilidades de inclusão do tema prevenção à violência de gênero nas aulas de Ciências - Matareli, Débora Cristina Garcia (2024)
In a world marked by rising rates of violence, especially gender-based violence, schools are emerging as possible spaces to help promote awareness and prevention. The science curriculum, focused on health in elementary school, has the potential to transform this context. The documentary research highlighted a significant gap in the study of gender violence prevention. A qualitative approach was used with documentary research and content analysis, following the stages of pre-analysis, exploration of the material and treatment of the results. The analysis focused on the BNCC and the São Paulo Curriculum, in the parts corresponding to the teaching of Natural Sciences, complemented by a complete analysis of the booklet “Violence against women is not normal”. The analysis revealed that, although the curriculum documents address important aspects of health and prevention, there is a lack of explicit discussion of gender violence and gender equality. In the BNCC, topics such as individual and collective health are discussed, but gender-based violence is completely omitted. In the São Paulo Curriculum, there is a significant emphasis on health and prevention, but again, gender-based violence is not addressed. The absence of gender violence themes in official curricula reflects a 'blatant silence' that must be overcome, as well as highlighting the need to integrate these discussions transversally and continuously into the school curriculum, promoting an education that informs and transforms. The research concludes that it is essential to include themes of gender-based violence in the school curriculum in order to promote active and critical citizenship. It recommends updating curriculum documents, continuing training for educators, creating safe environments in schools and using tools such as Pedagogical Dialogical Talks to enrich educational practice. With these strategies, it is possible to promote an inclusive and transformative education, contributing to the construction of a fairer and more equal society.